Interventions for the prevention and management of neck/upper extremity musculoskeletal conditions: a systematic review. Issue 5 (14th September 2006) - Boocock, M G; McNair, P J; Larmer, P J; Armstrong, B; Collier, J; Simmonds, M; Garrett, N
Abstract : Considered from medical, social or economic perspectives, the cost of musculoskeletal injuries experienced in the workplace is substantial, and there is a need to identify the most efficacious interventions for their effective prevention, management and rehabilitation. Previous reviews have highlighted the limited number of studies that focus on upper extremity intervention programmes. The aim of this study was to evaluate the findings of primary, secondary and/or tertiary intervention studies for neck/upper extremity conditions undertaken between 1999 and 2004 and to compare these results with those of previous reviews. Relevant studies were retrieved through the use of a systematic approach to literature searching and evaluated using a standardised tool. Evidence was then classified according to a "pattern of evidence" approach. Studies were categorised into subgroups depending on the type of intervention: mechanical exposure interventions; production systems/organisational culture interventions and modifier interventions. 31 intervention studies met the inclusion criteria. The findings provided evidence to support the use of some mechanical and modifier interventions as approaches for preventing and managing neck/upper extremity musculoskeletal conditions and fibromyalgia. Evidence to support the benefits of production systems/organisational culture interventions was found to be lacking. This review identified no single-dimensional or multi-dimensional strategy for intervention that was considered effective across occupational settings. There is limited information to support the establishment of evidence-based guidelines applicable to a number of industrial sectors.